2017
DOI: 10.7860/jcdr/2017/26190.10562
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Patient’s Satisfaction with Phlebotomy Services in NABH Accredited Neuropsychiatric Hospital: An Effective Tool for Improvement

Abstract: Even though the overall patient's satisfaction was high, there were areas which needed our attention such as waiting time for phlebotomy procedure, lack of proper sitting arrangement, techniques of sample collection, knowledge of universal precautions etc. Appropriate corrective and preventive actions were taken to solve the problems. Thereby, feedback proved effective in maintenance and improvement of phlebotomy services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The degree of satisfied patients rose by 12.75% from 85.00% to 97.75%. This was better than in a previous study where 94% of patients were satisfied with the phlebotomy services [9]. This significant improvement may have been due to the ITPS, which automatically provided labeled tubes when the subjects checked in instead of the staff labeling them manually when drawing blood.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The degree of satisfied patients rose by 12.75% from 85.00% to 97.75%. This was better than in a previous study where 94% of patients were satisfied with the phlebotomy services [9]. This significant improvement may have been due to the ITPS, which automatically provided labeled tubes when the subjects checked in instead of the staff labeling them manually when drawing blood.…”
Section: Discussionmentioning
confidence: 63%
“…It was reported that there was a 19% decrease in WT after changes were made to the collection of materials, the LabTracker automated database system was improved with wait time calculators and real-time information regarding patient status, and lower-complexity appointments were streamlined [8]. Gupta et al also concluded that analyzing the feedback of root causes was effective at maintaining and improving phlebotomy services [9]. Several studies have used Lean Six Sigma with DMAIC (define, measure, analyze, improve, and control) to identify potential factors affecting a phlebotomist's daily routine, and reported improvements in the WT [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…23 A recent study of 1,200 hospital patients from India found that only 27% of phlebotomies were achieved with just one needle prick, most requiring two or three attempts. 24 Medical staff, particularly anaesthetists and physicians, are familiar with being asked to help with blood taking from patients in whom other staff have failed. While there are clearly multiple different factors contributing to the success or failure of phlebotomy, we believe that there needs to be a focus on the 'elephant in the room' missing from recent studies on, and courses in, phlebotomy: the significance of needle or cannula direction.…”
Section: Resultsmentioning
confidence: 99%
“…Phlebotomy requires quality control and appropriate education to prevent complications, such as ecchymosis at the site of puncture, syncope, nerve damage, bleeding, infection, hemoconcentration from prolonged tourniquet use, edema, thrombosis, and pain 8,9. Phlebotomy accuracy and first puncture success have been associated with higher patient satisfaction 10. New technologies can assist in successfully identifying veins for phlebotomy and I.V.…”
Section: Adjunctive Vascular Assessment Toolsmentioning
confidence: 99%